2015
DOI: 10.1097/qad.0000000000000823
|View full text |Cite
|
Sign up to set email alerts
|

Interacting partners of macrophage-secreted cathepsin B contribute to HIV-induced neuronal apoptosis

Abstract: Objective HIV-1 infection of macrophages increases cathepsin B secretion and induces neuronal apoptosis, but the molecular mechanism remains unclear. Design We identified macrophage secreted cathepsin B protein interactions extracellularly and their contribution to neuronal death in vitro. Methods Cathepsin B was immunoprecipitated from monocyte-derived macrophage supernatants after 12 days post-infection. The cathepsin B interactome was quantified by label-free tandem mass spectrometry and compared to uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 56 publications
1
30
0
Order By: Relevance
“…Previous studies from our laboratory have demonstrated that HIV infection of macrophages and microglia induces secretion of cathepsin B and neurotoxicity (Rodriguez-Franco et al 2012; Cantres-Rosario et al 2015; Zenón et al 2015). However, the mechanism of cathepsin B release in HIV-1 infected macrophages is not known.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies from our laboratory have demonstrated that HIV infection of macrophages and microglia induces secretion of cathepsin B and neurotoxicity (Rodriguez-Franco et al 2012; Cantres-Rosario et al 2015; Zenón et al 2015). However, the mechanism of cathepsin B release in HIV-1 infected macrophages is not known.…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of increased cathepsin B secretion by macrophages have been extensively studied in our laboratory (Rodriguez-Franco et al 2012; Zenon et al 2014; Cantres-Rosario et al 2015; Zenón et al 2015). The MDM cultures with decreased cathepsin B secretion levels after HIV infection observed in our experiments have captured our attention since they also have low levels of ROS/RNS after HIV infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results confirm previous studies that show that HIV infection and cocaine use have a direct effect on increasing the expression of CATB (Zenón et al 2014 ). Although in this study we could not compare the effect of HAND on CATB expression due to limited number of samples, previous studies confirmed an increased CATB levels with HAND (Cantres-Rosario et al 2015 ).…”
Section: Resultsmentioning
confidence: 70%
“…One of the most recent studies investigating DMF and its possible role in treating HAND looks at lysosomal dysfunction and the release of neurotoxic cathepsin B from infected macrophages. Increased cathepsin B release has been evidenced in HIV-infected macrophages and promotes neuronal apoptosis [282][283][284] and infected macrophages treated with DMF showed decreases in HIV-1 replication, cathepsin B secretion and ROS/RNS production [285]. DMF has consistently shown evidence of reducing HIV-1 replication in macrophages and inhibiting the release of neurotoxic compounds in vitro, but conflicting results on neuronal cell viability prevents a definitive conclusion of DMF's role in HAND therapy.…”
Section: Dimethyl Fumaratementioning
confidence: 99%